(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
Health encompasses the overall condition of mental, physical and social wellbeing. and it goes beyond simply being free from illness or disease. Children’s health is a complex topic. With the use of NFHS 4th and 5th round data, the child health profile is examined with the support of number of dimensions and parametres to examine degree of disparity that prevails across states and Union Territories of India. It has been discovered that the rates of infant mortality, malnourished children and under-five mortality have declined noticeably declined over time. The creation and validation of an Indian Composite Dimension Index (CDI) are the main topics of this research. This index, which is prepared using dimensions like child health dimension and Nourishment dimension. Child health Dimension includes parametres like Infant Mortality Rate and Under five mortality rate. Nutritional Dimension includes Anaemia, underweight childreen, wasting, stunted and severly wasted parameters. Pregnancy among underage women impact on the infant mortality rate, while programs for maternity care, Child vaccination programme, vitamin-A supplementation, greater literacy rate of women and childhood treatment diseases significantly lower the infant mortality rate. As therefore, it could be leveraged by legislators, healthcare professionals, and other child welfare stakeholders to track and enhance child health across time as well as place.